THE SIGNIFICANCE OF CREATIVE TOURISM SERVICES FOR THE STATE TOURISMSECTOR (Universal International Scientific Journal, 2026)
Creative tourism has emerged as a transformative force within the global tourismindustry. Unlike conventional mass tourism, it emphasizes active participation, cultural co-creation, andexperiential engagement between tourists and host communities. This paper examines the significanceof creative tourism services for the state tourism sector across economic, cultural, and strategicdimensions. The findings demonstrate that creative tourism generates higher per-capita tourist spending,creates sustainable employment, preserves intangible cultural heritage, and enhances destinationcompetitiveness. Policy recommendations are proposed for governments seeking to integrate creativetourism into national tourism strategies.
Keywords: creative tourism; state tourism policy; cultural economy